Islamic Game Based Learning: An Innovative Approach To Increase Student Interest and Engagement at SD Negeri 2 Peseng - Jumatriadi (Institute of Educational, Research, and Community Service, 2024)
This study aims to analyse the impact of Islamic game-based learning on increasing students' interest and engagement in learning. This research uses a quantitative approach with a quasi-experiment method with a pretest-posttest control group design. The sample of this study was grade VI students of SD Negeri 2 Peseng totalling 33 students. Data collection techniques used surveys, rating scales, interviews, observations, and documentation. Data analysis techniques used statistical analysis and qualitative analysis. The results showed that Islamic game-based learning significantly increased students interest and engagement in learning in the experimental group. On the other hand, there was no significant difference in students' interest and engagement before and after learning in the control group that used conventional learning. This shows that the innovative approach of Islamic game-based learning has a positive impact in increasing students' interest and engagement